Nasal Symptoms Reduction and Decreased Neutrophilia in Japanese Cedar Pollinosis With Prophylactic Treatment With a Combination of Montelukast, Fexofenadine, and Fluticasone Nasal Spray. Issue 4 (July 2019) - Otsuka, Hirokuni; Otsuka, Kuninori; Matsune, Shoji; Okubo, Kimihiro
Background and Objective: We reported neutrophil-associated tissue damage in cedar pollinosis subjects with refractory nasal symptoms prior to pollinosis season. Because the leukotriene receptor antagonist, montelukast, can inhibit neutrophil recruitment and activation, we investigated its effects on symptom relief and nasal neutrophilia in pollinosis subjects in the preseason. Methods: In the pollinosis preseason, symptomatic (PreSyP, n = 149) and asymptomatic subjects (PreAsP, n = 145) were prophylactically treated, and in season symptomatic subjects (InSyP, n = 134) were treated. Individuals were assigned to 1 of 2 treatment protocols: administration of cetirizine and fluticasone nasal spray (Cet-Flu) or montelukast, fexofenadine, and fluticasone nasal spray (Mo-Fex-Flu). Differences in symptom relief and inflammatory cell infiltration in nasal swabs were investigated. Results: In pollen season, 59% of PreSyP subjects given Cet-Flu and 88% of those treated with Mo-Fex-Flu had none or mild symptoms ( P  < .00001). In PreAsP subjects in season, 71% of Cet-Flu and 98% of Mo-Fex-Flu recipients had none to mild symptoms ( P  < .0000001). The proportions of subjects in the PreSyP group with nasal swabs with neutrophils 1+ to 3+ before and after treatment by Mo-Fex-Flu were 59% and 18%, respectively ( P  < .0001), and in PreAsyP, subjects with neutrophils 2+ to 3+ were 17% and 5%, respectively ( P  = .034). In PreSyP, a significant reduction in the percentage of subjects with mast cells >1+ was seen following both Cet-Flu ( P  = .027) and Mo-Fex-Flu ( P  = .0014) treatments. Conclusion: In PreSyP and PreAsP subjects, treatments with Mo-Fex-Flu were more effective than Cet-Flu to reduce nasal symptom scores. These effects were associated with reduction in the number of neutrophils and mast cells in nasal swabs.